(untitled) (Vietnam Journal of Community Medicine, 2026)
ABSTRACT Objective: To investigate changes in the surface skin temperature of the lower abdominal region following filiform needle acupuncture at bilateral Sanyinjiao (SP6) and Xuehai (SP10) acupoints in healthy volunteers Subject and method: Thirty-one healthy volunteer students who met the inclusion criteria were recruited for the study. This was a clinical interventional study employing a before-and-after comparison without a control group. Results: In the hypogastric region, at time point T1, the mean temperature change was 0.2 ± 0.7 °C, which was not statistically significant (p = 0.1). At T2 and T3, there was a clear increase in temperature, with mean changes of 0.4 ± 0.7 °C, which were statistically significant (p = 0.02 and p = 0.04, respectively). At the skin surface corresponding to bilateral Sanyinjiao (SP6), temperature changes were observed but were not statistically significant at any of the three time points. At Xuehai (SP10), at T1, both acupoint sites showed an insignificant increase in temperature. However, at T2 and T3, temperature increases were notable, with mean changes of 0.8 ± 1.3 °C on the right and 1.0 ± 1.2 °C on the left, which were statistically significant (p = 0.03 and p = 0.01, respectively). After acupuncture, vital signs such as pulse rate and forehead temperature showed no significant changes compared to baseline. Conclusion: There was a statistically significant increase in the surface skin temperature of the hypogastric region following filiform needle acupuncture at bilateral Sanyinjiao (SP6) and Xuehai (SP10) acupoints using the “burning mountain fire” manipulation technique. Significant temperature changes were also recorded at the Xuehai (SP10) acupoints after acupuncture.